2019
DOI: 10.3389/fbioe.2019.00332
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Bacterial Cellulose Nonwoven by Poly(fluorophenol) to Improve Its Hydrophobicity and Durability

Abstract: The present study aims to improve the hydrophobicity and durability of bacterial cellulose (BC) nonwoven by functionalization with poly(fluorophenol). To this end, laccase was first entrapped onto BC and then used to polymerize the fluorophenol {4-[4-(trifluoromethyl) phenoxy] phenol} in-situ. The polymerization of fluorophenol by laccase was confirmed through 1H NMR and MALDI-TOF analyses. The effect of poly(fluorophenol) on BC nonwoven was determined by evaluation of the surface hydrophobicity and olephobici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The average WCA value was obtained by measuring five different spots on the surface of each sample. Next, the water absorption time measurement was performed according to Song et al (2019). A 0.01 % Methylene blue (C.I.…”
Section: Water Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The average WCA value was obtained by measuring five different spots on the surface of each sample. Next, the water absorption time measurement was performed according to Song et al (2019). A 0.01 % Methylene blue (C.I.…”
Section: Water Resistancementioning
confidence: 99%
“…8f) was further increased. This could be due to the strong adhesion between BC nanofibers and proteins which decreased the water absorption, as evidenced in the water resistance analysis (Song et al 2019), and the enhanced processability of proteins by the addition of glycerol (Wang et al 2017). On the other hand, entrapping glycerol only was not sufficient to improve the dimensional stability of BC (Fig.…”
Section: Dimensional Stabilitymentioning
confidence: 99%
“…In this regard, previous studies have demonstrated the ability of laccase to mediate the coupling of different fluorophenol molecules (FP) onto lignocellulose fibers and lignin model substrates, resulting in an increased hydrophobicity. The best results were found when 4- [4-(trifluoromethyl)phenoxy]phenol (4,4-F3MPP) (Figure 1C) was used as a substrate (Kudanga et al, 2010;Acero et al, 2014;Wu et al, 2016;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…40,41 In another work, functionalization of BC with poly(fluorophenol) to tune the hydrophobicity and durability was also reported. 42 However, most of the reported methods for the preparation of amphiphilic BC membranes involve complex multistep chemical processes and are not always environmentally friendly. Also, the overall efforts to utilize BC or modified BC for the intended purpose are limited.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, modification of BC membrane by alkoxysilanes resulted in an amphiphilic membrane and was successfully used to separate surfactant stabilized oil in water and water in oil emulsions 40,41 . In another work, functionalization of BC with poly(fluorophenol) to tune the hydrophobicity and durability was also reported 42 . However, most of the reported methods for the preparation of amphiphilic BC membranes involve complex multistep chemical processes and are not always environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%